Conflict and Perspectives: The Social Construction of Chinese Ethnic Citizens against Natives in Surakarta, Indonesia after the May 1998 Riots - Yustia Atsanatrilova Adi; Mohammad Thoriq Bahri (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2023)
With over 1300 ethnic groups and 700 languages, Indonesia is one of the most varied countries in the world. One of those ethic is the Chinese, who have lived in Indonesia for almost 500 years due to international trade, which encourages mixed marriages. Since the 1700s, the Chinese and natives are working together to chase away the European colonial, and that relationship is developed into a deeper and more formal relation in this modern day. Although, the national revolution caused by the economic crisis occurred in 1998, the locals are targeting Chinese ethics, and many of the killing and rape victims are Chinese ethic. This research analyzes the changes in the social construction from the perspective of Chinese ethic after the 1998 riots by using the qualitative framework, with the deep interview method. The sample is 11 indormants which came from two different generations OF THE CHINESE ETHNIC GROUPS with the purpose to have a more comprehensive analysis, from different perspectives. In general, there are differences in construction between the older and younger generations. As a result, the older generation views natives as an out-group, whilst the younger generation views natives as friends and family, implying that there are no disparities in identity and group between Chinese and indigenous. Differences in access to law enforcement and economic disparities are two of the most influential factors in the social construction of Chinese ethic perspectives among natives.